GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 15598 species occurrences available in GBIF matching the query: TaxonKey: Phoca vitulina Linnaeus, 1758 HasCoordinate: true HasGeospatialIssue: false BasisOfRecord: Human Observation or Machine Observation or Observation or Material sample or Living Specimen or Literature Occurrence or Unknown evidence or Specimen. The dataset includes 15598 records from 92 constituent datasets: 3 records from iziko South African Museum - Marine Mammal Collection (AfrOBIS). 2 records from Wildlife Sightings. 152 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD other mammal data up to current day. 555 records from Biological Records Centre - Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 2010 records from Norwegian Species Observation Service. 822 records from DOF 2001-2006. 116 records from PSM Vertebrates Collection. 4 records from Merseyside BioBank - North Merseyside Mammals (verified). 1 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 1 records from Wattenmeer-Safari (Wurster Watt). 1 records from Artenvielfalt der Nordsee - Sylt. 8 records from NYSM Mammals. 1 records from Inventario de la mastofauna en las reservas de la biosfera Desierto del Vizcaíno y Valle de los Cirios. 946 records from Atlas of Mammals in Ireland 2010-2015. 11 records from IWDG Ferry Survey sightings Data 2001 to 2013. 10 records from Marine Conservation Society - Seasearch Marine Surveys. 10 records from The Mammal Society - National Mammal Atlas Project, online recording. 16 records from BioFokus. 763 records from naturgucker. 208 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 30 records from European Seabirds at Sea (ESAS) bird sightings from 1980 to 2003.. 1082 records from Artdata. 21 records from Royal Netherlands Institute for Sea Research (NIOZ) - Kom Fyke Mokbaai. 7 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 1 records from National Trust for Scotland - NTS Properties Species Records 1800-2013. 1 records from Schatzinsel Wangerooge. 7 records from Mammalogy Collection - Royal Ontario Museum. 3 records from Données ONF Faune-Flore-FOnge. 16 records from NCSM Mammals Collection. 29 records from Cowan Tetrapod Collection - Mammals. 74 records from Norwegian Biodiversity Information Centre - Other datasets. 2133 records from DOF. 1314 records from UAM Mammal Collection (Arctos). 596 records from Highland Biological Recording Group - HBRG Vertebrates (not Badger) Dataset. 1297 records from SEAMAP - marine mammals, birds and turtles. 17 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Vertebrate Observation Records, other than Birds. Pre-2010 for Cumbria. 3 records from Geographically tagged INSDC sequences. 142 records from Scottish Wildlife Trust - Commissioned surveys and staff surveys and reports for SWT reserves. . 1 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 538 records from iNaturalist research-grade observations. 1 records from MVZ Hildebrand Collection (Arctos). 1 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 54 records from SBMNH Vertebrate Zoology. 1 records from Anymals+plants - Citizen Science Data. 2 records from A Biological Survey of the Waters of Woods Hole and Vacinity. 1 records from Atlantic Reference Centre (OBIS Canada). 2 records from Marine species distributions in Irish coastal waters. 8 records from PIROP (Shipboard Surveys). 74 records from UWBM Mammalogy Collection. 1 records from Merseyside BioBank - North Merseyside Mammals (unverified). 3 records from MSB Mammal Collection (Arctos). 26 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 1 records from Gesamtartenliste Bremerhaven, Helgoland und Sylt. 1 records from Mammals Specimens. 1 records from UCM Mammal Collection (Arctos). 1 records from Bay of Fundy Species List (OBIS Canada). 1 records from CNMA/Colección Nacional de mamíferos. 100 records from MVZ Mammal Collection (Arctos). 20 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 59 records from LACM Vertebrate Collection. 218 records from CAS Mammalogy (MAM). 36 records from Cumbria Biodiversity Data Centre - Norman and Florence Hammond records. Seawatch and coastal survey records.. 3 records from CUMV Mammal Collection (Arctos). 15 records from Field Museum of Natural History (Zoology) Mammal Collection. 1 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 2 records from Ireland's BioBlitz. 1 records from Mammals housed at MHNG, Geneva. 1 records from BioMar (EurOBIS). 3 records from Macaulay Library Audio and Video Collection. 61 records from Mammal collection, Natural History Museum, University of Oslo. 1 records from BioMar - LIFE project. 8 records from UMMZ Mammal Collection. 9 records from MSB Host Collection (Arctos). 20 records from NMNH occurrence DwC-A. 1 records from PReCAST Marine Mammal Sightings. 11 records from UAM Mammal Observations (Arctos). 1 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 1 records from Artenvielfalt der Nordsee - Helgoland. 13 records from Diveboard - Scuba diving citizen science observations. 1 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia. 17 records from RBINS collections. 3 records from Museum of Comparative Zoology, Harvard University. 4 records from KUBI Mammalogy Collection. 940 records from NPWS Seal Database. 7 records from Glasgow Museums BRC - Mammal records for Clyde Faunal Area, 1850 to 2007. 156 records from Inventaire National du Patrimoine Naturel : Mammifères de France. 1 records from Artenvielfalt der Nordsee - Bremerhaven (Dorum-Neufeld). 1 records from South Australian Museum Australia provider for OZCAM. 741 records from Centre for Environmental Data and Recording - Marine Data from Northern Ireland. 1 records from Tullie House Museum - Tullie House Museum Natural History Collections.. 9 records from UCLA Donald R. Dickey Bird and Mammal Collection. 1 records from John Muir Trust - Species Records for John Muir Trust Properties 2007-2009.
Keywords: GBIF; biodiversity; species occurrences